Reimplantable Microdrive for Long-Term Chronic Extracellular Recordings in Freely Moving Rats - Polo-Castillo, Leopoldo Emmanuel; Villavicencio, Miguel; Ramírez-Lugo, Leticia; Illescas-Huerta, Elizabeth; Moreno, Mario Gil; Ruiz-Huerta, Leopoldo; Gutierrez, Ranier; Sotres-Bayon, Francisco; Caballero-Ruiz, Alberto (Frontiers in Neuroscience, 2019)
Extracellular recordings of electrical activity in freely moving rats are fundamental to understand brain function in health and disease. Such recordings require a small-size, lightweight device that includes movable electrodes (microdrive) to record either a new set of neurons every day or the same set of neurons over time. Ideally, microdrives should be easy to implant, allowing precise and smooth displacement of electrodes. The main caveat of most commercially available microdrives is their relatively short half-life span, in average ranging from weeks to a month. For most experiments, recording days-weeks is sufficient, but when the experiment depends on training animals for several months, it is crucial to develop new approaches. Here, we present a low-cost, reusable, and reimplantable device design as a solution to extend chronic recordings to long-term. This device is composed of a baseplate that is permanently fixed to the rodent’s skull, as well as a reusable and replaceable microdrive that can be attached and detached from the baseplate, allowing its implantation and reimplantation. Reimplanting this microdrive is particularly convenient when no clear neuronal signal is present, or when the signal gradually decays across days. Our microdrive incorporates a mechanism for moving a 16 tungsten-wire bundle within a small ( 15 mm3) lightweight device ( 4 g). We present details of the design, manufacturing, and assembly processes. As a proof of concept, we show that recordings of the nucleus accumbens core (NAcc) in a freely behaving rat are stable over a month. Additionally, during a lever-press task, we found, as expected, that NAc single-unit activity was associated with rewarded lever presses. Furthermore, we also show that NAc shell (NAcSh) responses evoked by freely licking for sucrose, consistent with our previously published results, were conserved from a first implant to a second microdrive reimplant in the same rat, notably showing reimplantation is possible without overtly affecting the functional responses of the area of interest. In sum, here we present a novel microdrive design (low-cost, small size and light weight) that can be used for long-term chronic recordings and reimplanted in freely behaving rats.